THE IMPACT OF INFLUENCER INTERACTIVITY ON LOCAL SKINCARE PURCHASE INTENTION IN BATAM CITY WITH TRUST AS MEDIATION - Putra, Edy Yulianto; Khesi, Khesi; Purwianti, Lily; Anggraini, Ratih (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This study investigates the impact of influencer interactivity, influencer authenticity, motivation to use, online consumer behavior, and brand trust on purchase intention among local skincare users in Batam, utilising the technology acceptance model (TAM) as its theoretical framework. Conducted as a quantitative study, data was gathered via an online questionnaire distributed to 310 respondents and analysed using PLS-SEM. The findings reveal influencer interactivity positively impacts influencer authenticity, motivation to use, and online consumer behavior. While influencer authenticity positively affects motivation to use, it does not directly impact online consumer behavior. Motivation to use positively affects both online consumer behavior and brand trust, with online consumer behavior positively influencing brand trust. Furthermore, brand trust significantly impacts purchase intention and is a mediating variable. These findings offer practical implications for local skincare companies, emphasising the importance of leveraging influencer marketing strategies and adopting a technology acceptance approach to enhance business performance and consumer engagement.JEL: L82, M31, M37.